1990
DOI: 10.1093/intimm/2.12.1121
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cell-mediated immune responses to Plasmodium falciparum schizont antigens in adults from a malaria endemic area: CD8+ T lymphocytes inhibit the response of low responder individuals

Abstract: Plasmodium falciparum schizont extract and purified protein derivative were used to stimulate peripheral blood mononuclear cells obtained from healthy aparasitemic Gabonese individuals with lifelong exposure to malaria infection and non-Gabonese control subjects who have had had no clinical malaria. In vitro lymphoproliferation was measured by uptake of tritiated thymidine, while production of interleukin-2, interferon-gamma, and soluble CD8+ were measured by immunoenzymatic assays. Enumeration of interferon-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1

Year Published

1993
1993
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
3
6
1
Order By: Relevance
“…Taken together, these results suggest that CCD8^) DQrestricted cells may be activated during periods of malaria transmission to down-regulate the cellular proliferative response to PfMSPI, Seasonal variation in thesuppressiveeffects of CD8' cells has been reported previously [8] (CD8' eells isolated from malaria-exposed donors during the malaria transmission season had suppressive activity whereas cells isolated in the dry season did not), but ttie only other study of DQ-medialed suppression of responses to malaria antigens [7] was conducted in an area of year-round malaria transmission where sueh seasonal changes would nol be expected.…”
Section: Phenotype Of Responding Cellssupporting
confidence: 65%
See 2 more Smart Citations
“…Taken together, these results suggest that CCD8^) DQrestricted cells may be activated during periods of malaria transmission to down-regulate the cellular proliferative response to PfMSPI, Seasonal variation in thesuppressiveeffects of CD8' cells has been reported previously [8] (CD8' eells isolated from malaria-exposed donors during the malaria transmission season had suppressive activity whereas cells isolated in the dry season did not), but ttie only other study of DQ-medialed suppression of responses to malaria antigens [7] was conducted in an area of year-round malaria transmission where sueh seasonal changes would nol be expected.…”
Section: Phenotype Of Responding Cellssupporting
confidence: 65%
“…Previous studies have indicated that in some malariaimmune donors proliferative responses to crude schi/ont anligen pteparatiiins can be enhanced by removal of the CD8* lymphoeyle population from the culture system [6][7][8][9], but the effect of CD8' depletion on responses to defined malaria antigens has not been investigated. We have examined ibe phcEUit) pc of cells proHlerating in response to one such antigen, PfMSPI, The responding cell population appears lobe predominantly CD4' and HLA-DR-restricted, but a smaller population of CD8 ' eells -which may be HLA-DQ restricted can also respond.…”
Section: Phenotype Of Responding Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that a number of diverse parasitic species such as Toxoplasma (Susuki and Kobayashi 1981), Plasmodium (Mshana et al 1990), Trypanosoma (Tarleton 1988;Silva et al 1992), and Leishmania (Proudfoot et al 1995) exert an immunomodulatory activity causing potentially host-protective eector responses to be down-regulated. These anomalies are related to disturbances in the production and utilization of IL-2, activation of CD8+ suppressor T cells and the generation of indomethacin sensitive suppressor mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…fulcipurum SGE-2 Zairean strain was grown in vitro and when parasitaemia reached 10-12%, schizonts were isolated by centrifugation over 55% Percoll. A soluble extract (Pf SE) was prepared from schizonts as described earlier (Mshana, McLean & Boulandi 1990). Control antigen was similarly prepared using uninfected human red blood cells.…”
Section: Antigen Preparationsmentioning
confidence: 99%